Checklist of the brachyuran crabs (Crustacea: Decapoda) in the rocky subtidal of Vitória Archipelago, southeast coast of Brazil - Alves, Douglas Fernandes Rodrigues [UNESP]; Barros-Alves, Samara de Paiva [UNESP]; Cobo, Valter José; Lima, Daniel José Marcondes [UNESP]; Fransozo, Adilson [UNESP] (Pensoft Publishers, 2012)
Biodiversity can be useful as an ecosystem indicator for conservation and monitoring, through continuous assessment of its main properties including stability, primary productivity, exploitation tolerance and even global environmental changes. The main purpose of this study was to provide a checklist of the crabs associated with subtidal rocky bottoms at the Vitoria Archipelago, southeastern Brazilian coast. Monthly collections were carried out from February 2004 through January 2006 on three islands at the Vitória Archipelago (23°44'S-45°01'W). The crabs were hand-caught by SCUBA divers during the daytime, in rock subtidal. A total of 3084 individuals were caught, belonging to 42 species, 28 genera, and 12 families, highlighting Mithraculus forceps (1528) and Stenorhynchusseticornis (407) representing more than 60% of the sample. On the other hand, Dromia erythropus, Moreiradromia antilensis, Ebalia stimpsoni, Garthiope spinipes and Tumidotheres maculatus had only one individual sampled. © 2012 Check List and Authors.